2021
DOI: 10.3390/jdb9040058
|View full text |Cite
|
Sign up to set email alerts
|

The Development of SARS-CoV-2 Variants: The Gene Makes the Disease

Abstract: A novel coronavirus (SARS-CoV-2) emerged towards the end of 2019 that caused a severe respiratory disease in humans called COVID-19. It led to a pandemic with a high rate of morbidity and mortality that is ongoing and threatening humankind. Most of the mutations occurring in SARS-CoV-2 are synonymous or deleterious, but a few of them produce improved viral functions. The first known mutation associated with higher transmissibility, D614G, was detected in early 2020. Since then, the virus has evolved; new mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(63 citation statements)
references
References 207 publications
2
56
0
Order By: Relevance
“…8 shows a spike at position 484, which is where the E484K mutation has been found to lead to substantial antibody escape. [126] Other positions, such as 417, 501, and 681 have also been associated with potential immune-evasive mutations (i.e., N501Y, K417N/T, L452R) [172]. Interestingly, focusing on site 346, we found that a relatively greater reduction in predicted activity was associated with Omicron sequences which include of the R346K mutation.…”
Section: Resultsmentioning
confidence: 79%
“…8 shows a spike at position 484, which is where the E484K mutation has been found to lead to substantial antibody escape. [126] Other positions, such as 417, 501, and 681 have also been associated with potential immune-evasive mutations (i.e., N501Y, K417N/T, L452R) [172]. Interestingly, focusing on site 346, we found that a relatively greater reduction in predicted activity was associated with Omicron sequences which include of the R346K mutation.…”
Section: Resultsmentioning
confidence: 79%
“…4 and 5). The orf1a: P2287S mutation is present in the nsp3 PLpro papain-like protease whose function is to block host innate immune response and promote cytokine expression [33]. The increasing frequency of orf1a: P2287S mutation and its association in mild cases could possibly indicate an enhanced host immune response and reduced cytokine expression (potentially mitigating cytokine storm), leading to less severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, the limitation of the meagre number of partially vaccinated patients (n=23) in this study should be noted before drawing any conclusion. The third mutation in orf1a (T3255I) is present in the nsp4 protein, whose function is to produce double-membrane vesicles required to form a replication-transcription complex [33]. This mutation may play a role in reducing the formation of active replication-transcription complexes in the host cell, in turn reducing the viral load and explaining its association with the milder disease form.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutation rate of SARS-CoV-2 is ~10 -6 mutations/site/cycle, which is sufficient to cause more than one mutation per site during an infection period 1 . Especially, the frequency of manifold mutations in the spike (S) region is three times that of the entire genome 2 . With the vaccination starting from the end of 2020, the pandemic has been effectively alleviated.…”
Section: Introductionmentioning
confidence: 99%